2001
DOI: 10.1063/1.1367902
|View full text |Cite|
|
Sign up to set email alerts
|

Robustness of ultrathin aluminum oxide dielectrics on Si(001)

Abstract: Articles you may be interested inThermal annealing effects on the structure and electrical properties of Al 2 O 3 gate dielectrics on fully depleted SiGe on insulator

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 16 publications
0
87
0
Order By: Relevance
“…It is suggested that the amorphous Al 2 O 3 phase becomes metastable with respect to a crystalline alumina polymorph, due the nanometer size scale of the film/substrate combination. Since some of the uses for ALD Al 2 O 3 films include gate oxide for electronics, 3,4 protective barriers, 5 as well as potential coatings in energy materials, [6][7][8][9][10] it is critical to characterize these coatings on the nanoscale. For example, in the case of energy materials, there are recent reports of enhanced stability and extended cycling of Li-ion battery nanomaterials coated with ALD Al 2 O 3 thin films, [6][7][8][9][10] 9 This work assumes that the Al 2 O 3 coating is amorphous, as would be expected.…”
mentioning
confidence: 99%
“…It is suggested that the amorphous Al 2 O 3 phase becomes metastable with respect to a crystalline alumina polymorph, due the nanometer size scale of the film/substrate combination. Since some of the uses for ALD Al 2 O 3 films include gate oxide for electronics, 3,4 protective barriers, 5 as well as potential coatings in energy materials, [6][7][8][9][10] it is critical to characterize these coatings on the nanoscale. For example, in the case of energy materials, there are recent reports of enhanced stability and extended cycling of Li-ion battery nanomaterials coated with ALD Al 2 O 3 thin films, [6][7][8][9][10] 9 This work assumes that the Al 2 O 3 coating is amorphous, as would be expected.…”
mentioning
confidence: 99%
“…Al 2 O 3 is a well-known good oxygen diffusion barrier that may protect the Si surface from oxidation, 10,11 and Al 2 O 3 is thermodynamically stable in contact with Si. Similar to SiO 2 , Al 2 O 3 is also a good glass former; thus, if alloyed with ZrO 2 and HfO 2 , their amorphous structure can be stabilized during high temperature annealing.…”
mentioning
confidence: 99%
“…Many experimental studies of high-k materials such as aluminum oxide (Al 2 O 3 ), hafnium oxide (HfO 2 ), and zirconium oxide (ZrO 2 ) grown by atomic layer deposition (ALD) have been reported. [4][5][6][7][8][9][10][11][12][13][14] The ALD technique can control the uniformity and thickness of films on substrate surfaces at an atomic scale. 15,16 The important thing for the ALD process is the initial reaction between the molecule and surface, because it determines the high-k/surface interface structure.…”
Section: Introductionmentioning
confidence: 99%